Evaluation of Clinical Findings and Treatment Results of Coronavirus Disease 2019 (COVID-19) in Pediatric Cancer Patients: A Single Center Experience - Tolunay, Orkun; Çelik, Ümit; Arslan, Ilknur; Tutun, Bugra; Özkaya, Merve (Frontiers in Pediatrics, 2022)
Objective: Evaluation of clinical findings and treatment results of COVID-19 in pediatric cancer patients. Study design: The study was designed as a single-center retrospective observational study. Pediatric cancer patients with COVID-19 admitted to the University of Health Sciences Adana City Training and Research Hospital pediatric COVID-wards from October 2020 to October 2021 were included. Clinical data and demographic characteristics were retrieved from patient files. Results: A total of 45 pediatric cancer patients diagnosed with COVID-19 were included in the study. The mean age of the patients was 8.68±5.16 years (range 1.5 to 17.5), 62.2% were male, 37.8% were Turkish citizens and 62.2% were Syrian refugees. A total of 41 patients (91.1%) had Leukemia/lymphoma while 4 (8.9%) had solid tumors. The most common symptoms were fever (66.7%), respiratory (35.6%) and gastrointestinal symptoms (17.8%). Disease severity was evaluated as mild in 46.7%, moderate in 44.4% and severe in 8.9% of patients. Patients presented lymphopenia (88.9%), thrombocytopenia (73.3%), anemia (71.1) and neutropenia (62.2%). Mean hospital length of stay was 15.18±10.34 (range 6 to 62) days in overall and 9.5±2.39 (range 2 to 28) days in PICU. Intensive care unit admission rate was 8.9% and mortality rate was 4.4%. Median viral shedding period was 21 days (range 7 to 52). Conclusions: Our study reveals that the mortality rate, length of hospital stay and the need for intensive care of pediatric cancer patients with COVID-19 is higher than healthy children. Prospective studies with larger sample sizes are needed to further evaluate the clinical findings and treatment results of COVID-19 in pediatric cancer patients.